Mahasiswa dan GenAI: Mengadopsi atau Tertinggal! - Aulia Helmina Putri; Firda Nosita (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to explore the determinants of satisfaction with GenAI and students’ continuence intention to use GenAI to support their academic activities by integrating the Technology Acceptance Model (TAM) and Expectation Confirmation Theory (ECT). Data were collected through an online questionnaire distributed to university students from several higher education institutions in South Kalimantan, Indonesia. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS. The findings indicate that perceived usefulness and expectation confirmation significantly influence user satisfaction, which in turn enhances students’ continuance intention to use GenAI. In contrast, perceived ease of use does not have a statistically significant effect on either user satisfaction or continuance intention. Satisfaction derived from GenAI usage encourages students to continue integrating GenAI into their learning processes. These findings emphasize that GenAI has been widely accepted by tech-savvy students, who recognize its benefits and its ability to meet their performance expectations in supporting academic activities. As GenAI continues to evolve and improve its features, it increasingly aligns with users’ needs, positioning GenAI as a critical technological option that students may either continue to adopt or risk being left behind.